Keragaman Jamur Candida yang Ditemukan pada Rongga Mulut Pasien yang Terpasang Endotracheal Tube di Intensive Care Unit: Sebuah Penelitian Observasional - Nafiah; Kurnia Hayati Rahman; Cane Lukisari; Meralda Rossi Syahdinda (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2025)
Backgroud: Candida species are the most common cause of systemic and mucosal diseases. Candida species cause bloodstream infections that are more than 90% fungal. Objective: There are variations of candida worldwide, and 15 different species recognize pathogens and cause human diseases. The aim of the of the study to identify variation of Candida in patient installation of Endotracheal Tube in intensive care unit. Materials and Methods: We conducted this research using a cross-sectional design. The collect sample during 6 months perform by single oral medicine specialist. Identification variety of Candida using VITEK 2® compact. Result: Data was obtained using a sample of 83 patients who installed an endotracheal tube unit in Dr. Ramelan Naval Hospital from March until August 2024. Results: There was a sample of 51 (61.4%) infected with Candida, with various candida being Candida albicans 39 (76.5%), Candida Tropikalis 6 (11.8%), Candida ciferri 3 (5.9%), Candida Lucitaniae 2 (3.9%), and Candida Gullermondii 1 (1.9%). Conclusion: This study identified Candida Ciferii as a new variant of Candida in this locus, known as a new resisten of fluconazole.